EMPOWERING COMMUNITIES OF RUBBER TANK GROUPS THROUGH THE APPLICATION OF LIQUID SMOKING IPTEX AS A MATERIAL FOR LATEX LITI VILLAGE, CENTRAL KAHAYAN DISTRICT, DISTRICT OF PULANG PISAU DISTRICT, CENTRAL KALIMANTAN PROVINCE - Revianti Coenraad (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
Bukit Liti Village is one of the villages which is administratively located in Central Kahayan District, Pulang Pisau Regency, Central Kalimantan Province. Bukit Liti Village has an area of 9,461.10 Ha with population density has reached 925 people. The location is ± 35 km from the capital of Central Kalimantan Province, Palangka Raya and ± 130 km from the town Pulang Pisau, and ± 12 km from the capital district Kahayan Tengah. Villagers in Bukit Liti village welcomed community service activities organized by Palangka Raya University, in the future they hope to conduct regular PKM activities in the village. The output resulting from this PKM activity is 3 units of pyrolysis reactor to produce liquid smoke. The use of liquid smoke as a latex freezer gives a real impact to farmers that are environmentally friendly, effective as latex clotting, preventing and reducing the bad smell of rubber materials and improving the quality of rubber processed materials. At the end of this community partnership program, the implementing team will conduct an evaluation of the implementation by conducting a simple survey of community opinions regarding program implementation, as well as their expectations of future activities.